2022
DOI: 10.1126/sciadv.abq3917
|View full text |Cite
|
Sign up to set email alerts
|

Injection continuous liquid interface production of 3D objects

Abstract: In additive manufacturing, it is imperative to increase print speeds, use higher-viscosity resins, and print with multiple different resins simultaneously. To this end, we introduce a previously unexplored ultraviolet-based photopolymerization three-dimensional printing process. The method exploits a continuous liquid interface—the dead zone—mechanically fed with resin at elevated pressures through microfluidic channels dynamically created and integral to the growing part. Through this mass transport control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…[50,51] The resolution of the TOPS lithography system is comparable to different kinds of optical projection lithography such as DLP, or CLIP, which support the rapid fabrication of 3D hydrogel structures with a resolution of approximately 10-200μm. [34,36,39] ( Figure 7A ). In contrast to other work, which focuses on one regime (tensile or compression), TOPS-printed 3D structures simultaneously exhibit superior mechanical properties in both tensile regimes (strain of 2400%, stress of 130 kPa) and compression regimes (strain of 95%, and stress of 15MPa) with a high degree of recoverability.…”
Section: Discussionmentioning
confidence: 99%
“…[50,51] The resolution of the TOPS lithography system is comparable to different kinds of optical projection lithography such as DLP, or CLIP, which support the rapid fabrication of 3D hydrogel structures with a resolution of approximately 10-200μm. [34,36,39] ( Figure 7A ). In contrast to other work, which focuses on one regime (tensile or compression), TOPS-printed 3D structures simultaneously exhibit superior mechanical properties in both tensile regimes (strain of 2400%, stress of 130 kPa) and compression regimes (strain of 95%, and stress of 15MPa) with a high degree of recoverability.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3D printing of a multicomponent platform has remained challenging because of the difficulty of integrating different materials. A modified continuous liquid interface production (CLIP) method, termed injection CLIP, exploits the continuous liquid interface mechanically fed with resin through microfluidic channels . This technique can accelerate printing speeds to 5- to 10-fold over current methods, can use resins an order of magnitude more viscous than CLIP, and can readily pattern a single heterogeneous object with different resins in all Cartesian coordinates.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…A modified continuous liquid interface production (CLIP) method, termed injection CLIP, exploits the continuous liquid interface mechanically fed with resin through microfluidic channels. 3 This technique can accelerate printing speeds to 5-to 10-fold over current methods, can use resins an order of magnitude more viscous than CLIP, and can readily pattern a single heterogeneous object with different resins in all Cartesian coordinates. Castiaux et al used a PolyJet 3D printer with two commercially available materials to create a microfluidic device with integrated valves and pumps.…”
Section: ■ Fabrication Techniquesmentioning
confidence: 99%
“…Many strategies have been proposed to realize the 3D printing of thermosets (Supplementary Table 2). Some are utilizing vat polymerization-based 3D printing such as digital light process (DLP) [14][15][16] , stereolithography (SLA) 17 , and direct sound printing (DSP) 18 . For example, Kuang et al reported a single-vat grayscale-DLP method and a two-stage curing ink to obtain functionally graded thermosetting materials 15 .…”
mentioning
confidence: 99%